Research on the Dynamic Characteristics of the Gripper Mechanism with Multi Clearance Joints for Printing Machines - Wan Qi; Zhang Yongfang; Zhu Chenglong (Jixie chuandong)
The printing speed, registration accuracy and print quality of the printing machine are deeply affected by the dynamic characteristics of the gripper mechanism. The gripper mechanism is mostly composed of a cam mechanism and some connecting rods, where joint clearances inevitably exist. The stability, work efficiency and lifespan of the mechanism would be reduced by the joint clearances. Taking a cam-linkage mechanism as the research object, a dynamic model of the mechanism with multiple clearance joints was established. The effects of different clearance sizes, clearance joint positions, and the number of the clearance joints on the dynamic responses of the mechanism were analyzed. The results indicate that all the above factors have an impact on the transmission accuracy and stability of the gripper mechanism, and the interaction between multi clearance joints has a significant impact on the dynamic characteristics of the mechanism. This study provides reference for the structural optimization design of printing machines with clearance joints.